Kate skates - O'Connor, Jane; DiSalvo, DyAnne (Puffin Young Readers, an imprint of Penguin Group (USA) Inc. New York, 2013)
When Kate gets new, big kids' ice skates and gives her old ones to her little sister, she is surprised that the new ones are much harder to use